Analisis Pemberdayaan Perempuan Peternak Sapi Perah dalam Program Kartini Peternak Indonesia di Wilayah Kerja KPBS Pangalengan - Aiman, Rifdah Yasmin Mumtaazah; Mauludin, Mochamad Ali; Sulistyati, Marina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Women’s empowerment, particularly in the livestock subsector, is an important issue that continues to receive attention in Indonesia's social and economic development. The Kartini Peternak Indonesia Program was initiated to provide support to female farmers in overcoming the various challenges they face. This study aims to analyze the empowerment of female dairy farmers through the Kartini Peternak Indonesia Program, which has been implemented in the KPBS Pangalengan work area. The research method used is a case study with a qualitative approach, involving 27 informants, including female farmers and related stakeholders. The results of this study show that the program successfully enhanced the knowledge and skills of female farmers in livestock business management, as well as opened opportunities for business diversification. Additionally, the program contributed to the improvement of income and quality of life for female farmers, which in turn supports national food security. This study is expected to provide recommendations for further development in the empowerment of women in the livestock subsector.